Elucidating the Role of Interfacial Hydrogen Bonds on Glass Transition Temperature Change in a Poly(Vinyl Alcohol)/SiO2 Polymer‐Nanocomposite by Noncovalent Interaction Characterization and Atomistic Molecular Dynamics Simulations. Issue 21 (11th September 2020) - Panigrahi, Ritwik; Chakraborty, Souvik; Ye, Jun; Lim, Geraldine S.; Lim, Freda C. H.; Yam, Joachim Khin Hun; Wu, Linda Yongling; Chng, Shuyun; Prawirasatya, Melissa; van Herk, Alexander M.; Thoniyot, Praveen
Abstract: A thorough experimental investigation of polymer‐glass transition temperature ( T g ) is performed on poly(vinyl alcohol) (PVA) and fumed silica nanoparticle (SiNP) composite. This is done together with atomistic molecular dynamics simulations of PVA systems in contact with bare and fully hydroxylated silica. Experimentally, PVA‐SiNP composites are prepared by simple solution casting from aqueous solutions followed by its characterization using Fourier‐transform infrared spectroscopy (FTIR), dynamic mechanical analysis (DMA), and dynamic scanning calorimetry (DSC). Both theoretical and experimentally deduced T g are correlated with the presence of hydrogen bonding interactions involving OH functionality present on the surface of SiNP and along PVA polymer backbone. Further deconvolution of FTIR data show that inter‐molecular hydrogen bonding present between PVA and SiNP surface is directly responsible for the increase in T g . SiNP filler and PVA matrix ratio is also optimized for a desired T g increase. An optimal loading of SiNP exists, in order to yield the maximum T g increase arising from the competition between hydrogen bonding and crowding effect of SiNP. Abstract : Theoretically and experimentally deduced glass transition temperature, T g, shows direct correlation with hydrogen bonding interactions between nanoparticle surface groups and the groups on the polymer in the nanocomposite as shown by the deconvolution analysis of FTIR data. A maximum limit to this effect of T g increase can be attributed to the overcrowding effect caused by an overload of silica nanoparticle.